Association of diastolic and systolic blood pressure with depression: a cross-sectional study from NHANES 2005-2018 - Zhang, Huifeng; Xu, Ying; Xu, Yaying (Frontiers in Psychiatry, 2024)
Background Many studies worldwide have reported the association between mental health and blood pressure, but the results are mixed, and even contradictory. We aim to investigate the relationship between systolic and diastolic blood pressure and depression in the entire US population. Methods This study analyzed cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. All adults completed 3-4 blood pressure measurements after sitting quietly for 5 minutes. Depression was diagnosed based on the Patient Health Questionnaire (PHQ-9), with a score ≥10 defined as depression. Weighted logistic regression and restricted cubic splines (RCS) were used to assess the relationship between blood pressure and depression. Two-piecewise linear regression was used to determine the inflection point. Additionally, subgroup analyses and interaction tests were conducted to identify potential subgroups. Finally, two sensitivity analyses were conducted. Results A total of 26,581 American adults were included, with a mean age of 47.2 years, of whom 13,354 (49.54%) were male; 2,261 individuals were defined as depressed, with a weighted prevalence of 7.41%. All participants’ mean systolic blood pressure (SBP) was 121.7 mmHg, and the mean diastolic blood pressure (DBP) was 70.9 mmHg. RCS showed a nonlinear association between SBP and depression, while DBP showed a positive linear association with depression. Two-piecewise linear regression showed that the inflection point of the association between SBP and depression was 129.7 mmHg. Weighted logistic regression showed that after fully adjusting for depression-related risk factors, there was a significant positive correlation between per 10 mmHg increase in DBP and depression (OR: 1.06, 95% CI: 1.00-1.12, P=0.04); however, only on the left side of the inflection point, SBP tended to decrease the odds of depression (P =0.09). Furthermore, interaction analysis showed that the association between DBP and depression was significantly stronger in cancer patients (P for interaction=0.02); on the left side of the inflection point (<129.7 mmHg), current smokers also significantly interacted with SBP (P for interaction=0.018). Finally, two sensitivity analyses also supported our findings. Conclusion In the adult population of the United States, there is a positive linear association between DBP and depression, while the association between SBP and depression exhibits a significant threshold effect, maintaining SBP at 129.7 mmHg is associated with the lowest prevalence of depression.